2010
DOI: 10.1016/j.nurt.2009.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials in Traumatic Brain Injury: Past Experience and Current Developments

Abstract: Summary:In this article, we review past and current experience in clinical trials of traumatic brain injuries (TBIs), we discuss limitations and challenges, and we summarize current directions. The focus is on severe and moderate TBIs. A systematic literature search of the years from 1980 to 2009 revealed 27 large phase III trials in TBI; we were aware of a further 6 unpublished trials. Analysis of these 33 trials yielded interesting observations:• There was a peak incidence of trial initiations that occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
163
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 253 publications
(170 citation statements)
references
References 38 publications
(24 reference statements)
1
163
0
4
Order By: Relevance
“…S6); however, in the vast majority (up to 90%) of TBI incidents in humans, swelling and oedema are confined to the skull in nonpenetrating injuries 36 . We sought to use a focal injury, the mouse cortical cold injury model, which has previously been used extensively to study the dynamic of cerebral oedema formation [37][38][39] . This model has been shown to cause changes in caveolin-1, occludin and claudin-5 expression within the lesion site at various time points post-injury and highlights the dynamic changes that occur with respect to the BBB post-neuronal injury 20 .…”
Section: Discussionmentioning
confidence: 99%
“…S6); however, in the vast majority (up to 90%) of TBI incidents in humans, swelling and oedema are confined to the skull in nonpenetrating injuries 36 . We sought to use a focal injury, the mouse cortical cold injury model, which has previously been used extensively to study the dynamic of cerebral oedema formation [37][38][39] . This model has been shown to cause changes in caveolin-1, occludin and claudin-5 expression within the lesion site at various time points post-injury and highlights the dynamic changes that occur with respect to the BBB post-neuronal injury 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of these evidence-based recommendations are best applied in well-funded and well-equipped neurosurgical or neurotrauma centres [15][16][17] . The recent Benchmark Evidence from South American Trials: Treatment of Intracranial Pressure (BEST Trip) trial was based on standard recommendations for randomized clinical trials in high-income countries [18][19][20][21][22] . Results were far from expected because advanced monitoring tools used to guide treatments in high-income countries were not as successful in LMICs, and discussion within the global neurotrauma scientific community emerged after the publication of this study [23][24][25][26][27] .…”
Section: Epidemiology and Global Research In Tbimentioning
confidence: 99%
“…10 In the CRASH I trial (which included children older than 16 years of age) sites which had to obtain written informed consent took significantly longer to randomize patients and ultimately to administer study drug (3 hours vs. 4 hours). 31,32 Our study also showed substantial heterogeneity of intracranial injuries among children with moderate-tosevere TBIs. The implications of this may be important, as certain interventions may target specific types of intracranial injuries.…”
Section: Discussionmentioning
confidence: 52%